Antihypertensive Effects of Gmelina Arborea Roxb (Verbenaceae) Leaves Crude Aqueous Extract Fractions in Wistar Rats - LAGNIKA, LATIFOU (My University, 2015)
The present work was carried out to investigate the antihypertensive properties of fractions Gmelina arborea aqueous extract, one of the medicinal plants used in the treatment of arterial hypertension. Fractions of Gmelina arborea leaves were obtained by liquid-liquid extraction and by sephadex gel chromatography. The chemical screening and detection of anti-oxidant activity of extracts and fractions were performed by thin layer chromatography. Antihypertensive effect has been studied by administration of the extracts and fractions at the dose of 30mg/kg of body weight to wistar rats made hypertensive by L-NAME treatment. Rat arterial blood pressure was measured by carotid catheterization. Eight fractions named F1, F2, F3 and E1, E2, E3, E4, E5 were obtained. Altogether, flavonoïds, tannins, saponins, alkaloids, anthracens, napthtoquinons and coumarins were detected in the fractions. Except F3 fraction, all the other extracts and fractions have shown antioxydant activity. F2 fraction, E1 and E3 extracts induced significant reduction of rat mean arterial pressure from 165.5 ± 2.7mm Hg to respectively 121± 1,1mm Hg, 128.5± 2,8mm Hg and 134.2±4 mm Hg. These data suggest that the antihypertensive activity of the leaves of Gmelina arborea could be related to flavonoids compounds alone or synergistically with alkaloids and tannins compounds.
Keywords: High blood pressure; gmelina arborea; antioxidant; traditional medicine.